Biological and ecological characteristics of Chlaenius inops Chaudoir (Coleoptera: Carabidae) - Son, Le Anh; Lan, Tran Ngoc; Con, Vu Quang (Academia Journal of Biology, 2013)
Ground beetle Chlaenius inops Chaudoir is an important predator in limiting bollwowm Helicoverpa armigera (Hubner) population on rice, groundnut, maize in Nghe An privince. The beetle Ch. inops has the four following development stages: eggs are white; larvae black, head yellowish brown; pupation in the soil or on the ground. Five and six days after exposed and mated, the beetle female began laying eggs; eggs are laid scatteringly, and the females have three laying egg series in their life-span, with 17-30 eggs laid in each course. The different instar larvae of the beetle Chlaenius inops consumed the different number of preys, namely the first, second, third instar larvae and adult kill 1.89, 3.72, 4.86 and 3.38 preys on average, respectively. The research also showed that the number of preys has an influence on function reaction ot the beetle, especially of the third instar larva. Temperature and relative huminity have the considerable effect on the development of ground beetle Chlaenius inops, viz. the life cycle in duration is 60-75 days and 36-48 days at 20oC, 82% RH and 28oC, 73% RH, respectively.